Fluoride concentrations of milk, infant formulae, and soy‐based products commercially available in Brazil. (9th October 2015) - Nagata, Mariana Emi; Delbem, Alberto Carlos Botazzo; Kondo, Karina Yuri; de Castro, Luciene Pereira; Hall, Kevin Bruce; Percinoto, Célio; Aguiar, Sandra Maria Herondina Coelho Ávila; Pessan, Juliano Pelim
Abstract: Objectives: To assess the fluoride (F) content in commercially available milk formulae in Brazil and to estimate the F intake in children from this source in the first year of life. Methods: Samples of cow's milk ( n  = 51), infant formulae ( n  = 15), powdered milk ( n  = 13), and soy‐based products ( n  = 4) purchased in Araçatuba (Brazil) had their F content measured using an ion‐specific electrode, after hexamethyldisiloxane‐facilitated diffusion. Powdered milk and infant formulae were reconstituted with deionized water, while ready‐to‐drink products were analyzed without any dilution. Using average infant body masses and suggested volumes of formula consumption for infants 1‐12 months of age, possible F ingestion per body mass was estimated. Data were analyzed by descriptive analysis. Results: Mean F content ranged from 0.02 to 2.52 mg/L in all samples. None of the cow's milk provided F intake higher than 0.07 mg/kg. However, two infant formulae, one powdered milk, and one soy‐milk led to a daily F intake above the suggested threshold for fluorosis when reconstituted with deionized water. Assuming reconstitution of products with tap water at 0.7 ppm F, two infant formulae, five powdered milk, and four soymilks led to daily F intake ranging from 0.108 to 0.851 mg/kg. Conclusions: The results suggest that the consumption of some brands of infant formulae, powdered milk, and soy‐based milk in the first year of age could increase the risk of dental fluorosis, reinforcing the need for periodic surveillance of the F content of foods and beverages typically consumed by young children.